Very Late Pathological Responses to Cobalt–Chromium Everolimus‐Eluting, Stainless Steel Sirolimus‐Eluting, and Cobalt–Chromium Bare Metal Stents in Humans - Mori, Hiroyoshi (J Am Heart Assoc, 2017)
BACKGROUND: The “very late” clinical outcomes for durable polymer drug‐eluting stents and bare metal stents (BMSs) have been shown to be dissimilar in clinical studies. Conceptually, the long‐term vascular compatibility of BMSs is still regarded to be superior to drug‐eluting stents; however, no pathologic study to date has specifically addressed this issue. We evaluated the very late (≥1 year) pathologic responses to durable polymer drug‐eluting stents (cobalt–chromium [CoCr] everolimus‐eluting stents [EESs] and stainless steel sirolimus‐eluting stents [SS‐SESs]) versus BMSs (CoCr‐BMSs). METHODS AND RESULTS: From the CVPath stent registry, we studied a total of 119 lesions (40 CoCr‐EESs, 44 SS‐SESs, 35 CoCr‐BMSs) from 92 autopsy cases with a duration ranging from 1 to 5 years. Sections of stented coronary segments were pathologically analyzed. Inflammation score and the percentage of struts with giant cells were lowest in CoCr‐EESs (median inflammation score: 0.6; median percentage of struts with giant cells: 3.8%) followed by CoCr‐BMSs (median inflammation score: 1.3 [P<0.01]; median percentage of struts with giant cells: 8.9% [P=0.02]) and SS‐SESs (median inflammation score: 1.7 [P<0.01]; median percentage of struts with giant cells: 15.3% [P<0.01]). Polymer delamination was observed exclusively in SS‐SESs and was associated with increased inflammatory and giant cell reactions. The prevalence of neoatherosclerosis with CoCr‐EESs (50%) was significantly less than with SS‐SESs (77%, P=0.02) but significantly greater than with CoCr‐BMSs (20%, P<0.01). CONCLUSIONS: CoCr‐EESs, SS‐SESs, and BMSs each demonstrated distinct vascular responses. CoCr‐EESs demonstrated the least inflammation, near‐equivalent healing to BMSs, and lower neointimal formation. These results challenge the belief that BMSs have superior biocompatibility compared with some polymeric coated drug‐eluting stents and may have implications for future stent design.